PENINGKATAN HASIL BELAJAR MATEMATIKA DENGAN MENERAPKAN MODEL PEMBELAJARAN TEKNIK JIGSAW BERBANTUAN DAKON DI SEKOLAH DASAR - Wulandari, Wulandari; Bistari, Bistari; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to improve student learning outcomes by applying the Jigsaw cooperative learning model to the eye Mathematics class material count arithmetic operations School IV Dasar Negeri 03 Pontianak City. using the number media. The research method used is descriptive method with forms the research used is classroom action research. Data source This research is 34 class IV students and the data are is guu ability in planning and implementing learning and the learning outcomes of each cycle applying a cooperative model of jigsaw techniques to mathematics learning. The analysis technique used is the formula average calculation. This research was carried out as many as Ill cycles and each cycle consists of two meetings with the results obtained are 1) the teacher's ability to plan learning begins and cycle I viz 2.68, second cycle is 3.40 and second cycle is 3.67, 2) the ability of the teacher carry out learning starting from the first cycle is 2.58, the second cycle is 3.36 and cycle III which is 3,58; 3) the learning outcomes of students starting from the first cycle is 69.55 sikus II is 76.91 and cycle III is 85.07. Â Keywords: Improving, Learning Outcomes, Mathematical Learning, Cooperative Model, Jigsaw Technique